Supracalcaneal-calcaneal arthroereisis (a review of literature) - Zazirniy, Igor; Kovalchuk, Vitaliy; Lyabakh, Andrey; Grebenicov, Konstantin (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
Artroerez - a surgical procedure whose purpose is to limit specific movement in the joint. When the subtalar implant artroereze use, which is installed in the sinus tarsi and which serves as a prosthesis to limit excessive eversion of the subtalar joint. Despite the improvement in surgical technique and materials, subtalar artroerez remains a matter of debate, particularly with regard to age, indications, timing of operations, and other procedures.